Biscay and Beyond? Prehistoric Voyaging between Two Finisterres. Issue 4 (2nd October 2017) - Callaghan, Richard; Scarre, Chris
Summary: The Atlantic peninsulas of western Europe present intriguing cultural parallels that reach back into later prehistory. Furthermore, direct evidence of interconnections from the fifth millennium BC is revealed by the movement of specific materials such as Iberian variscite. Brittany and Galicia were key nodes within this potential network of maritime interaction, but debate continues as to the routes that were chosen and the navigational abilities involved. Did early seafarers keep close to the coast and did long journeys involve many intermediate landfalls? Or did crews venture direct crossings of the Bay of Biscay? In the absence of surviving evidence for the kinds of vessel likely to have been used by Neolithic seaborne navigators, modern wind and current data are here used to generate models indicating journey times for small sea‐going craft powered only by oars, following the coastal or the direct route. The results are discussed within the context of selected material flows (jadeitite, variscite, copper, Beakers) and against a background of potentially changing maritime technology.